COMBINATION OF DEXAMETHASONE IMPLANT AND ANTI-VEGF IN THE MANAGEMENT OF DIABETIC MACULAR EDEMA: A SYSTEMATIC REVIEW - Paramita, Ursula Natasya Pradnya; Tania, Tania; Clarissa, Clarissa; Salsabila, Salma (Majalah Oftalmologi Indonesia, 2023)
Background: Anti Vascular Endothelial Growth Factor (anti-VEGF) and dexamethasone implant (DEX) are suggested as the first and second-line therapy for Diabetic Macular Edema (DME). However, persistent DME were found after six months of routine anti-VEGF injection. Intravitreal steroids have the advantage to control the inflammatory component of DME. Combining intravitreal anti-VEGF and DEX may reduce macular edema more effectively and more quickly theoretically. Hence, we aim to review the efficacy of adding DEX to anti-VEGF in treating DME. Methods: Literatures were obtained using comprehensive searching on PubMed and Proquest using the keywords “Dexamethasone implant”, “anti-VEGF therapy”, and “Diabetic Macular Edema” including their synonyms between 2018 to 2023. Non-English studies, animal studies, review articles, case studies, and editorial letters were excluded. This result was presented following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines. Results: A total of 3 studies with 265 eyes were included. All of the studies had Central Foveal Thickness (CFT) and Best Corrected Visual Acuity (BCVA) as the main outcomes. Improved CFT was seen in all of the studies (all p<0.05) with ∆CFT (200,40 μm in 6 months and 413 μm in 12 months). Most studies showed improved visual acuity after 8 months of injections which were shown by ∆BCVA (8,84 letters in 6 months and 21,6 letters in 12 months) and increased intraocular pressure as an adverse effect of steroids. Conclusion: Combination of DEX and anti-VEGF showed improvement in CFT and BCVA. Further studies are required due to the controversial intravitreal steroids’ ocular adverse effect.